Collecting and Classifying Large Scale Data to Build an Adaptive and Collective Memory: a Case Study in e-Health for a Pro-active Management - Nicolas, Singer; Sylvie, Trouilhet; Ali, Rammal; Jean-Marie, Pécatte (IntechOpen, 2011)
None